Histopathological features of gastric cancer of a tertiary care hospital - Díaz Lazo, Aníbal Valentín (2020)
Objective. to describe the histopathological features of gastric cancer from a tertiary care hospital. Methods. a descriptive, retrospective, cross-sectional study was conducted in 103 patients. The inclusion criteria were: being 18 years of age or older, have upper digestive endoscopy study and pathological study with a diagnosis of adenocarcinoma. Exclusion criteria: not having and examination and/or a gastric biopsy result, having a diagnosis compatible with other types of malignancies. The data were drained in a questionnaire from the epidemiological surveillance registry of the Hospital’s oncology service. Results. the average was 67 years. Gastric cancer presented in 83,5 % in over 50 years of age. The most affected age group was between the sixth and eighth decade (54, 6 %), with a similar frequency of presentation in men (50,5 %) and women (49,5 %). The sites of gastric involvement were: anthro corporeal in 71 (68,9 %), antrum 23 (22,3 %), pylorus 5 (4,9 %), gastric fundus 2 (1,9 %) and cardia 2 (1,9 %). Only in 50 (100 %) cases was a histological study carried out, of which the most common variety of gastric cancer found was the diffuse type in 33 (66 %) cases and the intestinal type in 17 (34 %). Poorly differentiated adenocarcinoma occurred in 24 (48 %) cases; moderately diffentiated in 15 (30 %); mixed carcinomas in 6 (12 %) cases. Conclusions. it is concluded that diffuse gastric adenocarcinoma with involvement of more than on anatomic region is the most frequent and the poorly differentiated histological type is the most common.